Assisting Schools Partnership in Ternate to Design an e-Portfolio: Pendampingan Perancangan Portofolio Digital (e-Portfolio) bagi Sekolah Mitra di Kota Ternate - Fatma Hamid; Nurdin Abdul Rahman; Saprudin Saprudin (Mattawang: Jurnal Pengabdian Masyarakat, 2022)
This article is a part of the Community Service Program (PKM) in assisting the design and use of multimedia for schools partnership in Ternate. This article focuses on assisting schools partnership in ternate to design an e-portfolio. This PKM activity involves two schools partnership that have B grade accreditation, namely school X and school Y. This PKM activity includes a preliminary survey, training, mentoring, evaluation and reflection. Based on the results of observations and assessments of the resulting e-Portfolio product, it shows that this PKM activity has a positive impact on increasing the competence of schools partnership teachers in designing e-Portfolios. In general, the achievement of teacher competence in designing e-Portfolios can be categorized as good.